Business Process Management of Vehicle Sales and After-Sales Services: A Case Study in an Indonesian Auto Company - Billie Enceil; Gunawan Wang (Politeknik Siber Cerdika Internasional, 2026)
Background: XYZ, Inc., a medium-sized automotive company specializing in vehicle sales and repair services, faces significant operational challenges arising from manual processes, fragmented information systems, and limited interdepartmental coordination. These inefficiencies result in extended processing times, reduced data accuracy, and a negative impact on customer satisfaction (CSAT). Objective: This study aims to analyze and redesign the vehicle sales and repair service processes at XYZ, Inc. using the Case Study framework. BPMN 2.0 was employed to identify bottlenecks, misalignments among sales, repair, and inventory units, and sources of manual data entry inefficiency. Methods: This research adopts a qualitative descriptive case study design following the five-stage BPM Lifecycle (identification, discovery, analysis, redesign, and implementation). Data were collected through structured interviews, direct observation, and document review. BPMN 2.0 was used to model as-is and to-be processes, and performance gaps were measured by comparing actual versus expected processing times across key activities. Results: The redesigned processes led to faster processing times, a reduction of errors, and improved data sharing among departments. Post-project assessments showed that BPM enhances customer experience by facilitating faster service delivery and response. Additionally, performance analytics were implemented to track top-level metrics such as cycle time, data quality, and repair response time. Conclusion: BPM implementation at XYZ, Inc. resulted in significant reductions in processing time for vehicle sales and repair activities, including a reduction in Sales Order Preparation from 18.5 to 9 hours and Parts Ordering from 8 to 2 hours. The redesigned processes improved data accuracy, interdepartmental integration, and overall operational efficiency. These findings demonstrate the practical value of the BPM Lifecycle approach in the automotive retail and service sector.